2022
DOI: 10.12890/2022_003246
|View full text |Cite
|
Sign up to set email alerts
|

Use of Midodrine in Heart Failure: Two Case Reports and a Review of the Literature

Abstract: Hypotension in patients with heart failure is much more frequent in daily clinical practice than the 10–15% reported in clinical trials. In patients with heart failure with reduced ejection fraction (HFrEF), hypotension frequently limits the initiation and up-titration of guideline-directed medical therapy (GDMT). Midodrine is a peripheral alpha-1 agonist and a vasopressor anti-hypotensive agent approved for the treatment of orthostatic hypotension. We describe two cases where midodrine was prescribed in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Firstly, in terms of hospitalization-related outcomes, the midodrine group exhibited fewer ER visits but more ICU stays, respiratory failures, all hospitalizations, and mortality. Until now, only case reports ( Hajjiah et al, 2022 ) or case series ( Zakir et al, 2009 ) have addressed midodrine usage in heart failure. In one case series ( n = 10) ( Zakir et al, 2009 ), midodrine usage was associated with fewer total hospital admissions and total hospital days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, in terms of hospitalization-related outcomes, the midodrine group exhibited fewer ER visits but more ICU stays, respiratory failures, all hospitalizations, and mortality. Until now, only case reports ( Hajjiah et al, 2022 ) or case series ( Zakir et al, 2009 ) have addressed midodrine usage in heart failure. In one case series ( n = 10) ( Zakir et al, 2009 ), midodrine usage was associated with fewer total hospital admissions and total hospital days.…”
Section: Discussionmentioning
confidence: 99%
“…However, a poster presentation ( Scoma et al, 2021 ) indicated significantly higher all-cause mortality at 6 months following hospitalization in the midodrine group compared to the non-midodrine group (HR:6.7, 95% CI:5.2%–8.5%). There have been some recent case reports showing potential benefits (at least in terms of blood pressure improvement and a higher likelihood of GDMT) ( Hajjiah et al, 2022 ; Shiu et al, 2022 ). However, these studies were only case series with small sample sizes, lacking matched controls, and limited to short-term follow-ups.…”
Section: Introductionmentioning
confidence: 99%